2006
DOI: 10.1621/nrs.04024
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor transcriptional coregulator RIP140

Abstract: The nuclear receptor superfamily comprises ligand-regulated transcription factors that control various developmental and physiological pathways.These receptors share a common modular structure and regulate gene expression through the recruitment of a large set of coregulatory proteins.These transcription cofactors regulate, either positively or negatively, chromatin structure and transcription initiation. One of the first proteins to be identified as a hormone-recruited cofactor was RIP140. Despite its recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 75 publications
0
52
0
1
Order By: Relevance
“…RIP140 was also shown to interact with many other nuclear receptors (NRs) and transcription factors (for a review see ref. 7). More recently, we demonstrated that RIP140 behaves as an Rb-like regulator of the E2F pathway by directly binding to E2Fs and repressing their transactivation potentials (8).…”
Section: Introductionmentioning
confidence: 99%
“…RIP140 was also shown to interact with many other nuclear receptors (NRs) and transcription factors (for a review see ref. 7). More recently, we demonstrated that RIP140 behaves as an Rb-like regulator of the E2F pathway by directly binding to E2Fs and repressing their transactivation potentials (8).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was isolated as an estrogen receptor α partner, though it interacts with many other NRs (Augereau et al 2006a). It consists of 1,158 amino acids in human and 1,161 amino acids in mouse, with 83% homology between the two sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Our work is mainly focused on RIP140 (receptor-interacting protein of 140 kDa, also known as NRIP1), a nuclear protein of 1,158 amino acids, initially identified as a transcription cofactor of estrogen receptors and shown to regulate energy homeostasis in metabolic tissues (see ref. 8 for a review). RIP140 is an atypical coregulator because, despite its recruitment by agonist-liganded nuclear receptors, it exhibits a strong transcriptional repressive activity.…”
mentioning
confidence: 99%